AGGREGATE ANALYSIS OF FDI IMPACT ON GROWTH IN SELECTED PHARMACEUTICAL FIRMS - Pasha, MOHAMMAD AZMATH; MAHABOOB, MOHAMMAD (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
For many economies, foreign direct investment is a major source of capital funds and a primary source of outside funding. The liberalization of FDI rules in India presents both opportunities and risks for businesses. Additionally, it has been noted that FDI affects the productivity, growth, and efficiency of businesses in addition to its effect on the national economy. The most significant problem is that most nations have trouble selecting FDI policies. This is primarily because of competing goals, such the need for both equitable income distribution and quick growth. In this study, the influence of foreign direct investment (FDI) on the expansion of particular companies is evaluated in terms of currency earnings, sales, profit, and assets. Pharmaceutical company aggregates based on foreign direct investment are taken into consideration for this analysis. The study is conducted between 2000–01 and 2009–2010, a span of ten years